Thực hiện phép tính (-2/11+3/13)-(-3/13+9/11)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 2/9 - (1/20 + 2/9)
= 2/9 - 1/20 - 2/9
= (2/9 - 2/9) - 1/20
= 0 - 1/20
= -1/20
b) -3/14 + 2/13 + (-25/14) + (-15/13)
= (-3/14 - 25/14) + (2/13 - 15/13)
= -2 - 1
= -3
c) -3/11 + 11/8 - 3/8 + (-8/11)
= (-3/11 - 8/11) + (11/8 - 3/8)
= -1 + 1
= 0
d) 3/8 + (-1/4) - (7/12 - 1/6)
= 1/8 - 5/12
= -7/24
e) (1/3 + 12/67 + 13/41) - (79/67 - 28/41)
= 1/3 + 12/67 + 13/41 - 79/67 + 28/41
= 1/3 + (12/67 - 79/67) + (13/41 + 28/41)
= 1/3 - 1 + 1
= 1/3
a: =35/17-18/17-9/5+4/5
=1-1=0
b: =-7/19(3/17+8/11-1)
=7/19*18/187=126/3553
c: =26/15-11/15-17/3-6/13
=1-6/13-17/3
=7/13-17/3=-200/39
`a)3/5+(-4/9)`
`=3/5-4/9`
`=27/45-20/45`
`=7/45`
`b)3/5+2/5 . 15/8`
`=3/5 + 30/40`
`=3/5+3/4`
`=12/20+15/20`
`=27/20`
`c)7/2 . 8/13 + 8/13 . (-5/2)`
`=8/13 . (7/2 +(-5)/2)`
`=8/13 . 1`
`=8/13`
`d)-5/17 . (-9/23)+9/23 . (-22/17) + 11 9/23`
`=-5/17 . (-9/23) + 9/23 . (-1) . 22/17 + 11 + 9/23`
`=-5/17 . (-9/23) + (-9/23) . 22/17+11+9/23`
`= -9/23 ( -5/17 + 22/17)+11+9/23`
`= - 9/23 . 1+11+9/23`
`=-9/23+11+9/23`
`=(-9/23+9/23)+11`
`=0+11`
`=11`
a: =27/45-20/45=7/45
b: =3/5+30/40
=3/5+3/4
=12/20+15/20
=27/20
c: =8/13(7/2-5/2+1)=8/13*2=16/13
d: =9/23*5/17-9/23*22/17+11+9/23
=-9/23+11+9/23
=11
`@` `\text {Ans}`
`\downarrow`
`a.`
`A=(1/2-7/13-1/3)+(-6/13+1/2+1 1/3)`
`= 1/2 - 7/13 - 1/3 - 6/13 + 1/2 + 1 1/3`
`= (1/2 + 1/2) + (-7/13 - 6/13) + (-1/3 + 1 1/3) `
`= 1 - 1 + 1`
`= 1`
`b.`
`B=0,75+2/5+(1/9-1 1/2+5/4)`
`= 3/4 + 2/5 + 1/9 - 3/2 + 5/4`
`= (3/4+5/4)+ 1/9 + 2/5 - 3/2`
`= 2 + 1/9 - 11/10`
`= 19/9 - 11/10`
`= 91/90`
`c.`
`(-5/9).3/11+(-13/18).3/11`
`= 3/11*[(-5/9) + (-13/18)]`
`= 3/11*(-23/18)`
`= -23/66`
`d.`
`(-2/3).3/11+(-16/9).3/11`
`= 3/11* [(-2/3) + (-16/9)]`
`= 3/11*(-22/9)`
`= -2/3`
`e.`
`(-1/4).(-2/13)-7/24.(-2/13)`
`= (-2/13)*(-1/4-7/24)`
`= (-2/13)*(-13/24)`
`= 1/12`
`f.`
`(-1/27).3/7+(5/9).(-3/7)`
`= 3/7*(-1/27 - 5/9)`
`= 3/7*(-16/27)`
`= -16/63`
`g.`
`(-1/5+3/7):2/11+(-4/5+4/7):2/11`
`=[(-1/5+3/7)+(-4/5+4/7)] \div 2/11`
`= (-1/5+3/7 - 4/5 + 4/7) \div 2/11`
`= [(-1/5-4/5)+(3/7+4/7)] \div 2/11`
`= (-1+1) \div 2/11`
`= 0 \div 2/11 = 0`
a; (-5) + 11 + 17 + (-3)
= - 5 + 11 + 17 - 3
= - (5 + 3) + (11 + 17)
= - 8 + 28
= 20
\(A,\dfrac{7}{11}+\dfrac{5}{6}-\dfrac{-4}{11}-\dfrac{1}{6}\)
\(= (\dfrac{7}{11}+\dfrac{-4}{11})-(\dfrac{5}{6}-\dfrac{1}{6})\)
\(=\dfrac{3}{11}-\dfrac{2}{3}\)
\(= \dfrac{9}{33}-\dfrac{22}{33}\)
\(= \dfrac{-13}{33}\)
\(B,\dfrac{5}{9}.\dfrac{7}{3}+\dfrac{5}{9}.\dfrac{9}{13}-\dfrac{5}{9}:\dfrac{13}{5}\)
\(=(\dfrac{5}{9}.\dfrac{5}{9}:\dfrac{5}{9}).\dfrac{7}{3}+\dfrac{9}{13}-\dfrac{13}{5}\)
\(=(\dfrac{5}{9}.\dfrac{7}{3})+(\dfrac{9}{13}-\dfrac{13}{5})\)
\(=(\dfrac{5}{9}.\dfrac{21}{9})+(\dfrac{45}{65}-\dfrac{169}{65})\)
\(=\dfrac{35}{27}+\dfrac{-124}{65}\)
\(=\dfrac{2275}{1755}+\dfrac{-3348}{1755}\)
\(=\dfrac{-1073}{1755}\)
\(\left(\frac{-2}{11}+\frac{3}{13}\right)-\left(\frac{-3}{13}+\frac{9}{11}\right)\)
\(=\frac{-11}{11}+\frac{6}{13}\)
\(=\frac{-7}{13}\)